ANALISIS PENGARUH EARNING PER SHARE, HARGA EMAS DUNIA, INFLASI TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA PADA MASA PANDEMI COVID-19 - Ahmad Fairuzie; Arifin Siagian; Yosi Stefhani (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
This study aims to determine the simultaneous and partial effect of earnings per share, world gold prices, inflation on share prices of mining sector companies on the Indonesia Stock Exchange during the Covid-19 pandemic. The population in this study there are 47 mining sector companies listed on the Stock Exchange using purposive sampling method in sampling. Researchers set certain criteria in taking research samples and obtaining 32 companies as samples. This research was conducted during the Covid-19 pandemic during 2020. The data collection technique in this study used the documentation method by studying the company's financial statement records, stock price data, world gold price data, and inflation. The data analysis method in this study used multiple linear regression analysis with SPSS 25 program. The results showed that in the F-test simultaneously earning per share, world gold prices, inflation had a significant effect on stock prices of mining sector companies on the Indonesia Stock Exchange during the Pandemic. Covid-19. Meanwhile, the t-test results show that partially earnings per share (EPS) has a significant effect on the share price of mining companies on the Indonesia Stock Exchange during the Covid-19 pandemic. On the other hand, partially world gold prices and inflation have no significant effect on share prices of mining sector companies on the Indonesia Stock Exchange during the Covid-19 pandemic.